Understanding the COVID-19 pandemic impact on hospitality industry: an industry perspective on graduates’ employability in higher education / Wan Nor Bayah Wan Kamarudin ... [et al.] - Wan Kamarudin, Wan Nor Bayah; Mohd Fuza, Zatul Iffah; Mat Ghani, Amanina; Wan Nawawi, Wan Nazriah (Universiti Teknologi MARA, 2023)
Due to the adverse impact of COVID-19 on hospitality business operations and viability, industry viewpoints are essential to assessing the employability of recent graduates. Consequently, the aims of this study were to (1) grasp the effects of COVID-19 on the hospitality industry and (2) determine the impacts on hospitality graduates’ employability from an industrial perspective. Qualitative research was employed to obtain hospitality industry representatives’ opinions, and the data were analyzed utilizing a thematic approach with the Atlast.ti software. The COVID-19 significantly influenced the business operation, thus impacting graduate employability. Therefore, essential employability skills highlighted by industry needs, namely entrepreneurship skills, analytical or critical thinking, communication, and teamwork are vital for graduates’ employability. In addition, substantial knowledge has been pointed out based on participants’ prior experiences in these unprecedented circumstances. There are few empirical studies that have investigated the employability of hospitality graduates during or after the COVID-19 pandemic; nonetheless, this study presents valuable industry insights that can aid Higher Learning Institutions (HLI) in improving curricula, hence indirectly strengthening the employability of hospitality graduates. Conclusions and suggestions have been drawn in relation to industry viewpoints to solicit the interest of hospitality practitioners in higher education institutions and scholars.